Peran Artificial Intelligence Dan Promosi Karir Dalam Penilaian Kinerja Terhadap Budaya Meritokrasi Pegawai - Kurniawan Prambudi Utomo; Ananto Krisna Wardhana; Rachmat Fadly; Riris Lestiowati; Aprilia Puspasari; M Aziz Winardi N (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2026)
This study examines the role of Artificial Intelligence (AI) in performance evaluation and promotion systems and its implications for meritocratic culture within organizations. Using a quantitative approach, survey data were collected from employees and Human Resource (HR) professionals in institutions that have implemented AI-based systems. The relationships among AI utilization, promotion mechanisms, performance appraisal, and perceptions of meritocracy were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that higher levels of AI adoption significantly enhance transparency and consistency in performance evaluation. Technology-supported promotion systems are also more oriented toward individual competencies and achievements. However, these positive effects are strongly influenced by employees’ perceptions of fairness and trust in the system. The findings underscore that successful AI integration requires not only technological readiness but also effective governance to sustain a merit-based organizational culture